Peningkatan Mutu Pendidikan Karakter Melalui Peran Orang Tua Dalam Keluarga - Ni Komang Sutriyanti (UHN IGB Sugriwa Denpasar, 2016)
Characters are vital aspects for the national human resourcesÂ as their quality will determine the progress of the nation. The families are the main and elementary places for the character education.Â The good and bad relationship between husband and wife, parents and children, between children contributes to the success of the family education. It creates the interactional situation for the education. Implanting the character values is one of the ways to improve the character education to realize the quality human resources.